simplifique a expressão abaixo:
A)
![{10}^{ - 3} \times {10}^{5 } = \\ 10 \times {10}^{4} {10}^{ - 3} \times {10}^{5 } = \\ 10 \times {10}^{4}](https://tex.z-dn.net/?f=+%7B10%7D%5E%7B+-+3%7D+%5Ctimes++%7B10%7D%5E%7B5+%7D+%3D+++%5C%5C+10+%5Ctimes++%7B10%7D%5E%7B4%7D+)
B)
![{7}^{4} \times {7}^{ - 3 } \times {7}^{2} \div {7}^{3} \div {7}^{ - 2} = {7}^{4} \times {7}^{ - 3 } \times {7}^{2} \div {7}^{3} \div {7}^{ - 2} =](https://tex.z-dn.net/?f=+%7B7%7D%5E%7B4%7D++%5Ctimes++%7B7%7D%5E%7B+-+3+%7D++%5Ctimes++%7B7%7D%5E%7B2%7D++%5Cdiv++%7B7%7D%5E%7B3%7D++%5Cdiv++%7B7%7D%5E%7B+-+2%7D++%3D+)
Soluções para a tarefa
Respondido por
1
pode confiar está 100% certo
dudaah2411:
obgda ♥️
Perguntas interessantes
Geografia,
10 meses atrás
Português,
10 meses atrás
Português,
1 ano atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás